PELAKSANAAN MEDIASI PADA PENYELESAIAN PERCERAIAN DI PENGADILAN AGAMA KUNINGAN - Fitri Purnamasari; Diding Rahmat; Gios Adhyaksa (Universitas Kuningan, 2017)
AbstractThe author conducted this research with the background of the implementation of Mediation in Kuningan Religious Court in Kuningan. The purposes of writing this paper are to know how the Implementation on Divorce Settlement in Kuningan Religious Court and to know the factors that affect the success of mediation in the Kuningan Religious Court. The method used in this research is with empirical juridical approach using primary data and secondary data and data collection techniques are interviews, observation and literature study. The results of this research are the mediation arrangements set out in the Supreme Court Regulation (PERMA ) Number 1 Year 2016 about Mediation Procedures in Courts and more specifically stipulated in the Decree of the Chief Justice Number 108 / KMA / AK / VI / 2016 on Mediation Governance at the Court. Mediation is the means of dispute resolution through the negotiation process to obtain agreement of the Parties with the assistance of the Mediator. Mediator is a Judge or any other party who has a Mediator Certificate as a neutral party assisting Parties in the negotiation process to see possible dispute resolution without resorting to the disconnection or enforcement of a settlement. Its implementation has been regulated in Law Number 1 Year 1974 about concerning Marriage, Compilation of Islamic Law, and Supreme Court RegulationNumber 1 of 2016 concerning Mediation Procedure in Court. The conclusion of this thesis writing is Mediation which should be one of the alternative process of dispute settlement which can give greater access to justice to the parties in finding satisfactory dispute settlement and to fulfill the sense of justice, and become one of the effective instrument to overcome the problem of case buildup especially for the case Divorce, in the end has not been effectively implemented.Keywords: Mediation, Divorce, Marriage. AbstrakPenulis melakukan penelitian ini dengan latar belakang yaitu bagaimana pelaksanaan Mediasi pada Pengadilan Agama Kuningan. Tujuan penulisan ini untuk mengetahui bagaimana Pelaksanaan pada Penyelesaian Perceraian di Pengadilan Agama Kuningan dan untuk mengetahui bagaimana faktor-faktor yang memepengaruhi keberhasilan mediasi di Pengadilan Agama Kuningan. Metode yang digunakan dalam penelitian ini adalah dengan pendekatan yuridis empiris dengan menggunakan data primer dan data sekunder serta alat pengumpulan data yang digunakan melalui wawancara, observasi dan studi pustaka. Hasil penelitian ini adalah pengaturan mediasi diatur dalam Peraturan Mahkamah Agung (PERMA) Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan dan lebih spesifik diatur dalam Keputusan Ketua Mahkamah Agung Nomor : 108/KMA/AK/VI/2016 tentang Tata Kelola Mediasi di Pengadilan. Mediasi adalah cara penyelesaian sengketa melalui proses perundingan untuk memperoleh kesepakatan Para Pihak dengan dibantu oleh Mediator. Mediator adalah Hakim atau pihak lain yang memiliki Sertifikat Mediator sebagai pihak netral yang membantu Para Pihak dalam proses perundingan guna mencari berbagai kemungkinan penyelesaian sengketa tanpa menggunakan cara memutus atau memaksakan sebuah penyelesaian. Pelaksanaannya telah di atur dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkwinan, Kompilasi Hukum Islam, dan Peraturan Mahkamah Agung Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan. Kesimpulan dari penulisan skripsi ini adalah Mediasi yang seharusnya menjadi salah satu alternatif proses penyelesaian sengketa yang dapat memberikan akses keadilan yang lebbesar kepada para pihak dalam menemukan penyelesaian sengketa yang memuaskan dan mmemenuhi rasa keadilan, serta menjadi salah satu instrumen efektif mengatasi masalah penumpukan perkara khususnya untuk perkara perceraian, pada akhirnya belum efektif dilaksanakan.Kata Kunci : Mediasi, Perceraian, Perdata